Phase relations in circuits with autoparametric oscillations - EG Usmanov , RCh Karimov , MU Idrisxodjaeva, MB Zubaydullaev (International Journal of Advanced Science and Technology, 2020)
This article deals with the issues of amplitude-phase relations in auto-parametric circuits with a stable S-shaped volt-ampere characteristic with a wide area of the incident section, and assesses the regularity of changes in the shape, width, and slope of the incident section of the amplitude-phase characteristic when the chain parameters vary.